Bis{2′-[1-(2-hydroxy-5-chlorophenyl)ethylidene]-benzohydrazido- κ2O,N2′}bis(pyridine-κN)zinc(II) - Ali, Hapipah Mohd; Yamin, B.M.; Khamis, N.A. (International Union of Crystallography, 2004)
The title compound, [Zn(C15H13ClN2O 2)2(C5H5N)2], is a centrosymmetric monomer with octahedral geometry about the Zn atom. The molecule is stabilized by intermolecular C-H⋯O and C-H⋯Cl interactions, so forming a three-dimensional network. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.